Insight into trypanosomosis (Surra) of Indian livestock: Recent updates - SINGH, VEER; MAHARANA, BISWA RANJAN (The Indian Journal of Animal Sciences, 2018)
Surra, caused by Trypanosoma evansi, is an economically important disease of a wide range of domestic and wild animals, and is most widely distributed. It is a potentially fatal disease causing huge economic losses to the livestock owners in terms of morbidity, mortality, abortion, infertility, reduced milk yield and also by interfering with vaccination programme in India. Due to sub clinical nature of the disease, it has been underestimated in cattle and buffaloes. Emergence of atypical cases of human trypanosomiasis has created an alarming situation and indicates a possible zoonotic threat in future. Accurate diagnosis of surra is extremely essential to identify animals for treatment, to assess the prevalence of the disease and to avoid indiscriminate usage of trypanocidal drugs. Diagnosis of surra still suffers from low sensitivity and specificity. There is an urgent need for sensitive cost effective penside diagnostic that can be applicable and affordable to smallholder farmers in endemic regions. The present review addresses various aspects of surra with special emphasis on disease epidemiology, emerging issues, current diagnostic trends, chemotherapeutics and preventive measures to limits its prevalence in livestock.